2008
DOI: 10.1097/mcg.0b013e31803d0f80
|View full text |Cite
|
Sign up to set email alerts
|

Management of Occluded Uncovered Metallic Stents in Patients With Malignant Distal Biliary Obstructions Using Covered Metallic Stents

Abstract: Insertion of a covered EMS is an effective and safe treatment for an occluded uncovered EMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 17 publications
6
39
0
2
Order By: Relevance
“…Occluded SEMS further result in biliary stone/sludge formation and recurrent cholangitis [85]. In addition, SEMS present for years in the biliary system might cause serious vascular complications in liver transplant patients [86].…”
Section: Self-expandable Metallic Sent Placementmentioning
confidence: 99%
“…Occluded SEMS further result in biliary stone/sludge formation and recurrent cholangitis [85]. In addition, SEMS present for years in the biliary system might cause serious vascular complications in liver transplant patients [86].…”
Section: Self-expandable Metallic Sent Placementmentioning
confidence: 99%
“…Many retrospective series have demonstrated that it developed in 5%-40% of patients who underwent an endoscopic palliative treatment with SEMS [14][15][16][17][18][19] . The causes of occluded SEMS include tumor ingrowth, overgrowth, sludge/debris formation and stent migration ( Table 1).…”
Section: Occlusionmentioning
confidence: 99%
“…Many studies have shown that one fourth of all SEMS occlusions resulted from tumor overgrowth [14][15][16][17][18][19] . Because tumor can grow and invade over both ends of the stent, covered and uncovered SEMSs have an equal chance to develop tumor overgrowth.…”
Section: Occlusionmentioning
confidence: 99%
See 2 more Smart Citations